Efek Teratogenik Asam Salisilat pada Perkembangan Morfologi Fetus Mencit (Mus musculus L.) Swiss Webster - Dewi ciselia; Arum Setiawan; Sri Nita; Salni Salni (Faculty of Mathtmatics and Natural Sciences, 2014)
One of teratogenic chemical is salicylic acid. Therefore it is necessary to do a research on the tera-togenic effects of salicylic acid on the morphological development of the mice fetal.The aims of this study is to find the teratogenic effect of salicylic acid On The Morphology Development Of Mice.This research used randomized complite design 5 treatment and 5 replicated. The data were analyzed with one way Anova and then with Duncan’s test. Salicylic acid administrated intraperitoneal injection at a dosage 40 mg/kgbw, 60 mg/kgbw, 80 mg/kgbw in 6,7, and 8 days of gestation. The remaining animals were used as an untreated control, and placebo were given by aquades. at 18th days of gestations, twenty five pregnant mice were sacrificed and caesarian sectioned to remove the fetuses and then check fetus body wight, life fetus, dead fetus and morfology fetus.The results of this study showed that the dose of 80mg/kgbb and 60mg/kgbb salicylic acid cause pregnant mice weight, the administration of salicylic acid from 40mg/kgbb dose can reduce the average weight of the fetus, the provision of 40mg/kgbb salicylic acid may decrease the number the implantation of the fetus and also the number of living fetuses, administration of salicylic acid with 80mg/kgbb doses can cause fetal death (IUFD), giving 60mg/kgbb salicylic acid will cause open eyelids disability, giving salicylic acid does not cause embryo-nic desorption, disability in the legs, tail, NTD and also ceiling blemish (cleft palate) and kidney defects in the fetus.